A portrait of the early and differential mental health impacts of the COVID-19 pandemic in Canada: Findings from the first wave of a nationally representative cross-sectional survey - Jenkins, Emily K.; McAuliffe, Corey; Hirani, Saima; Richardson, Chris; Thomson, Kimberly C.; McGuinness, Liza; Morris, Jonathan; Kousoulis, Antonis; Gadermann, Anne (Preventive medicine, 2021)
Evidence on the population-level mental health impacts of COVID-19 are beginning to amass; however, to date, there are significant gaps in our understandings of whose mental health is most impacted, how the pandemic is contributing to widening mental health inequities, and the coping strategies being used to sustain mental health. The first wave of a repeated cross-sectional monitoring survey was conducted between May 14–29, 2020 to assess the mental health impacts of the pandemic and to identify the disproportionate impacts on populations or groups identified as experiencing increased risks due to structural vulnerability and pre-existing health and social inequities. Respondents included a nationally representative probability sample (n = 3000) of Canadian adults 18 years and older. Overall, Canadian populations are experiencing a deterioration in mental health and coping due to the pandemic. Those who experience health, social, and/or structural vulnerabilities due to pre-existing mental health conditions, disability, income, ethnicity, sexuality, and/or gender are more likely to endorse mental health deterioration, challenging emotions, and difficulties coping. This monitoring study highlights the differential mental health impacts of the pandemic for those who experience health, social, and structural inequities. These data are critical to informing responsive, equity-oriented public health, and policy responses in real-time to protect and promote the mental health of those most at risk during the pandemic and beyond. •The mental health consequences of the COVID-19 pandemic are not distributed equally.•The COVID-19 pandemic is contributing to widening mental health inequities.•A public health approach, inclusive of mental health promotion is needed.•Syndemics theory can inform action to respond to mental health inequities.